A phenomenological investigation of gymnasts' lived experience of imagery - Post, P. G.; Wrisberg, C. A. (The Sport Psychologist, 2012)
Phenomenological interviews were conducted with ten female collegiate gymnasts (M age = 22.2; SD = 1.68 yr) to determine their lived experience of sport imagery. Qualitative analysis of the interview data revealed a total of 693 meaning units and produced a final thematic structure consisting of five major dimensions: preparing for movement; mentally preparing; feeling the skill; controlling perspective/speed/ effort; and time and place. Among the results not reported in previous studies were athletes` manipulations of imagery speed for various purposes, the incorporation of abbreviated body movements during imagery to accentuate the feel of the action, correcting inadvertent mistakes in an imaged performance, and the imaging of upcoming segments of a serial skill during execution. The findings extend previous sport imagery research and provide suggestions for sport psychology consultants working with elite gymnasts.